2020
DOI: 10.1093/beheco/araa031
|View full text |Cite
|
Sign up to set email alerts
|

Full spectra coloration and condition-dependent signaling in a skin-based carotenoid sexual ornament

Abstract: Carotenoid-based traits commonly act as condition-dependent signals of quality to both males and females. Such colors are typically quantified using summary metrics (e.g., redness) derived by partitioning measured reflectance spectra into blocks. However, perceived coloration is a product of the whole spectrum. Recently, new methods have quantified a range of environmental factors and their impact on reflection data at narrow wavebands across the whole spectrum. Using this approach, we modeled the reflectance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Kervinen et al (2015) reported a decrease in the size of the red-eye combs of male black grouse (Lyrurus tetrix) at advanced ages. The comb color is due to red ketocarotenoids, but its size depends on circulating testosterone that expands the epidermis producing a larger but paler trait (i.e., negative correlation between trait redness and size; Harris et al 2020). Therefore, the smaller eye combs in older birds would probably be redder.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kervinen et al (2015) reported a decrease in the size of the red-eye combs of male black grouse (Lyrurus tetrix) at advanced ages. The comb color is due to red ketocarotenoids, but its size depends on circulating testosterone that expands the epidermis producing a larger but paler trait (i.e., negative correlation between trait redness and size; Harris et al 2020). Therefore, the smaller eye combs in older birds would probably be redder.…”
Section: Discussionmentioning
confidence: 99%
“…The two studies testing yellow traits did not detect an age‐related decline, whereas the grouse study reported only the analysis of the trait size, which is unrelated to color intensity (Harris et al. 2020). More recently, in male warblers ( Vermivora ), a study reported a reduction in the extension of the area of yellow plumage by analyzing three individuals during a short time‐lapse (i.e., 3 years; Baiz et al.…”
Section: Main Quadratic Model (1) Slope ± Se F Df Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample collection has previously been described in Harris et al, (2018Harris et al, ( , 2020. Briefly, black grouse were caught between January and May, between 2007 and 2008, using oat-baited walk-in traps at five lek sites in central Finland (lat.…”
Section: Sample Collectionmentioning
confidence: 99%
“…In this study, we sought to describe the structure of these spikes (Figure 1). These eye combs show large (>fivefold) size differences between the breeding and nonbreeding season within the same individual, while also exhibiting considerable variation across years and among individuals (Harris et al, 2018(Harris et al, , 2020). An eye comb's red colouration is thought to derive from carotenoid pigment deposition due to their characteristic reflectance spectra (Harris et al, 2020) and the presence of carotenoids in combs of related species, such as the Red Grouse, Lagopus lagopus (Mougeot et al, 2007).…”
mentioning
confidence: 99%